Histopathology of liver and kidney on broiler chicken exposed to heat stress and fed extract of Jaloh (Salix tetrasperma Roxb) - Sugito .; W Manalu; E Handharyani; Chairul . (Jurnal Ilmu Ternak dan Veteriner, 2007)
This research was conducted to study the effects of jaloh extract (Salix tetrasperma Roxb) on broiler chicken exposed to heat stress in constant temperature of 33 ± 1oC for 4 hours per day for 10 days. Fifteen chickens aged 20 days old (strain Cobb) were divided randomly into 5 groups. The first group was external control (tCP) of the chickens received neither heat stress nor jaloh extract. The second group was internal control (CP) representing chickens given heat stress without jaloh extract. The third, fourth, and fifth groups consisted of chickens given heat stress and 10 mg/kg BB of hexane (CP+Hek), ethyl acetate (CP+EtOAc), and ethanol (CP+EtOH) fractions, respectively. Heat stress and jaloh extract were given every day. Extract of jaloh were given 1 hour before temperature in the cage was raised. On 10th day of the experiment, 3 chickens were killed and necropted. Liver and kidney tissues from each treatment were analyzed for histological condition. The results indicated that heat stress can induce injury degeneration, necrosis, and infiltration of inflammation cells of liver and kidney. It is concluded that the hexane fraction of jaloh extract could protect the detrimental effects on heat stress. Key Words: Heat Stress, Extract Salix, Liver, Broiler Kidney